Quality of Potable Jar Water in Selected Food Establishments in Shahbagh and Ramna, Dhaka, Bangladesh - Biswas, Judhisthir; Supti, Mahima Hossain; Zerin, Tamanna (Stamford Journal of Microbiology, 2025)
Water plays a vital role in maintaining the health, hygiene, and well-being of all living beings. The presence of harmful microorganisms and chemical pollutants in water can lead to severe health consequences. This study aimed to evaluate the physicochemical characteristics and microbiological quality of drinking jar water obtained from various hotels located in the Shahbag and Ramna areas of Dhaka city, Bangladesh. In this case, pH, temperature, carbon dioxide (CO2), alkalinity, hardness, color, iron (Fe), chloride (Cl-), and odor were measured and observed. Moreover, microbiological assessments of drinking water samples were carried out. For achieving the microbiological assessment, methods of total viable bacterial count (TVBC), total coliform count (TCC), and total fecal coliform (TFC) were used. Microbes were presumptively identified by microscopic and colony morphology with biochemical profiling. It was found that the pH of all samples ranged from 6.5 to 7.4, Fe recorded from 0.15- 0.427 mg/l, and the concentration of Cl- ions was within the 0.5-1.7 range. In addition, the hardness ranged from 0.15- 0.427 mg/l, alkalinity 2.13-9.4 mg/l, color from 20-52, and most of the water samples were odorless. All of the above-mentioned parameters fall within the marginal range for the majority of water samples. The highest total viable bacterial count was found in the water of the AA hotel sample (2.22 × 10⁷ CFU/ml), also the highest fecal coliform count was found at the same hotel (30 CFU/100 ml), and the highest total coliform count was noted in the Ak hotel sample (30 CFU/100 ml). The detection of indicator microorganisms signifies potential fecal contamination and poses serious public health risks, thereby rendering the water unsafe for human consumption. The results emphasize the necessity of maintaining water quality for human consumption. Stam. J. Microbiol. 2025;15(1): 47-52